ENVIRONMENTAL PROTECTION IN THE FRAMEWORK OF INTERNATIONAL LAW: DEVELOPMENT AND PERSPECTIVES - Beci, Sander (European Scientific Journal, ESJ, 2014)
The paper concerns the international environmental law, and its main topics delineate: why an international dimension of environmental protection; the lack of direct referring on environmental protection in international law and the use of the state’s responsibility principle; a short view on the development of international environmental law; the latest developments and perspectives of environmental protection legislation; a short overview on the Albanian environmental normative regulation.